FRET-based acrylic nanoparticles with dual-color photoswitchable properties in DU145 human prostate cancer cell line labeling. (19th August 2016) - Keyvan Rad, Jaber; Mahdavian, Ali Reza; Khoei, Samideh; Janati Esfahani, Azam
Abstract: Dual-color photoswitchable fluorescent polymer nanoparticles have emerged as an important type of cell detectors. Here, dual-color acrylic nanoparticles containing spiropyran and azo-carbazole derivatives with remarkable photostability and photoreversibility were employed. These prominent properties were attributed to the covalent bonding between the incorporated chromophores and the polymeric matrix and provided efficient fluorescence resonance energy transfer phenomenon. The obtained nanoparticles were purified after dialysis and delivered into DU145 cancer cells. Trypan blue dye exclusion assays showed that these nanoparticles were biocompatible with no toxicity to the cells. Fluorescence microscopy images demonstrated that the prostate cancer cells containing nanoparticles exhibited excellent cell uptake with green and red fluorescence emissions after primary excitation at 410 nm and subsequent irradiation at 365 nm, respectively, depicting their dual-color characteristics. Graphical abstract: Highlights: Preparation of photoswitchable fluorescent polymer nanoparticles as cell detector. Dual-color acrylic nanoparticles containing spiropyran and azo-carbazole derivatives. FRET-based particles with improved photostability and photoreversibility. Reasonable cell compatibility and cell uptake to prostate cancer cells.